THE IMPACT OF BODY MASS INDEX ON TIME TO FULL FUNCTIONAL RECOVERY FOLLOWING TOTAL HIP ARTHROPLASTY: A SYSTEMATIC LITERATURE REVIEW - Maciej Osuch,; Maja Osuch,; Olga Tatarata,; Martyna Jaciubek,; Carmena Luty,; Amanda Abramowicz,; Magdalena Rumin,; Anna Kiełboń,; Zuzanna Olga Reklewska,; Kornelia Domagała, (International Journal of Innovative Technologies in Social Science, 2026)
Obesity represents a growing global health challenge with significant implications for orthopedic surgery outcomes. Total hip arthroplasty (THA) is one of the most common and successful procedures for treating end-stage hip osteoarthritis. The influence of high body mass index (BMI) on postoperative functional recovery requires our attention due to the seriousness of this issue. This systematic literature review aimed to evaluate the impact of BMI on time to full functional recovery following primary total hip arthroplasty, examining evidence from Polish and international studies. Outcomes assessed included Harris Hip Score (HHS), Hip disability and Osteoarthritis Outcome Score (HOOS), gait analysis parameters, complication rates, and time to functional independence. Based on the studies analyzed, it can be observed that elevated BMI primarily contributes to an increased risk of perioperative complications and revision surgeries. Short-term functional recovery (